PERILAKU AKTIVITAS TANAH UNTUK MENDUKUNG INFRASTRUKTUR DI MAJALENGKA DAN SEKITARNYA - -, Zufialdi Zakaria (Bulletin of Scientific Contribution, 2012)
Physical development of the region will always be associated with infrastructure studies. Construction plans in Kertajati International Airport, will bring the study of the infrastructure related to public facilities, which supports the international airport in West Java. Including a study of infrastructures are the foundation for buildings, roads, bridges, buildings, dams, etc., also the slope which is the result of slope stability design. This study discusses the behavior of the activity of high plasticity clay (CH) toward safety factor of slope and soil bearing capacity. Safety factor of slope is represented by value of FS (Factor of Safety) with a specified slope angle, so the increasing soil activity (A) is known relationship with a decrease in the value of the slope safety factor (FS). Soil bearing capacity is represented by the value of qa (allowable soil bearing capacity) for square and circular foundation type, so that the relationship of soil bearing capacity is decreasing with increasing value of soil activity. The study is expected to be developed, to facilitate the safety factor is the estimated slope and soil bearing capacity estimated by examining the number of activity as an early indicator. The relationship between the allowable soil bearing capacity (qa) for shallow foundations (of a square type) with soil activity (Skempton, and Seed) shows the equation qa = 7.89890 A (-1.01759) a negative relationship with correlation coefficient R = - 0754, and qa = 8.81669 A (-0.83957) a negative relationship with correlation coefficient R = - 0722. The relationship between the allowable soil bearing capacity (qa) for shallow foundation (of a circular type) with soil activity (Skempton, and Seed) shows the equation qa = 7.80513 A (-1.06644) a negative relationship with correlation coefficient R = - 0780, and qa = 8.77028 A (-0.88473) a negative relationship with correlation coefficient R = - 0722, it indicates that bearing capacity land values decline with increasing soil activity. The relationship between the security factor (FS) with 15o slope angle A activity figures show the equation FS = 1.517 A -0.79 with R ² = 0.625; The relationship between the safety factor (FS) with 30o slope angle A activity figures show the equation FS = 1.721 A - 0.78 with R ² = 0.64. Handling of expansive soil can be through soil improvement. To planning the foundation and slope infrastructures, is required safe design in accordance with assessment of soil bearing capacity and Factor of Safety (FS) of slopes, in order to avoid design failure.